Retroperitoneal Mature Cystic Teratoma in a Neonate: A Case Report - Prashant Sadashiv Patil; Paras Kothari; Abhaya Gupta; Vishesh Dikshit; Ravi Kamble; Geeta Kekre; Shahaji Deshmukh (EL-Med-Pub, 2016)
We report a case of retroperitoneal mature cystic teratoma in a 2-day-old neonate. Diagnostic and surgical procedure including its complexity and relevant literature review has been discussed.